State policies limiting premium surcharges for tobacco and their impact on health insurance enrollment. (27th October 2020) - Kaplan, Cameron M.; Kaplan, Erin K.
Abstract: Objective: The Affordable Care Act allows insurers to charge up to 50% higher premiums to tobacco users, making tobacco use the only behavioral factor that can be used to rate premiums in the nongroup insurance market. Some states have set more restrictive limits on rating for tobacco use, and several states have outlawed tobacco premium surcharges altogether. We examined the impact of state level tobacco surcharge policy on health insurance enrollment decisions among smokers. Study Design: We compared insurance enrollment in states that did and did not allow tobacco surcharges, using a difference‐in‐difference approach to compare the policy effects among smokers and nonsmokers. We also used geographic variation in tobacco surcharges to examine how the size of the surcharge affects insurance coverage, again comparing smokers to nonsmokers. Data Collection: We linked data from two components of the Current Population Survey—the 2015 and 2019 Annual Social and Economic Supplement and the Tobacco Use Supplement, which we combined with data on marketplace plan premiums. We also collected qualitative data from a survey of smokers who did not have insurance through an employer or public program. Principal Findings: Allowing a tobacco surcharge reduced insurance enrollment among smokers by 4.0 percentage points ( P = .01). Further, smokers without insurance through an employer or public program were 9.0 percentage points less likely ( P < .01) to enroll in a nongroup plan if they were subject to a tobacco surcharge. In states with surcharges, enrollment among smokers was 3.4 percentage points lower ( P < .01) for every 10 percentage point increase in the tobacco surcharge. Conclusions: Tobacco use is the largest cause of preventable illness in the United States. State tobacco surcharge policy may have a substantial impact on whether tobacco users choose to remain insured and consequently their ability to receive care critical for preventing and treating tobacco‐related disease.